Pelaksanaan Bagi Hasil Simpanan dan Pembiayaan Mudharabah Di BMT Al-Amanah Cabang Subang - Rina Lestari (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
The purpose of this study is to determine the Mudharabah profit sharing provisions according to the scholars, to know the implementation of Mudharabah savings and financing profit sharing, and to determine the impact of Mudharabah profit sharing and financing. The research method used is qualitative with an empirical approach. Data collection techniques used were observation, interviews, and documentation. In this study the data source consisted of primary data and secondary data. Primary data obtained from the field and secondary data consist of references, books, and sources from the internet. Research results show that Mudharabah savings and financing carried out at BMT Al-Amanah that is using mudlaabah mutlaqah and profit sharing ratio used is revanue sharing, according to ulama Mudharabah agreements may be carried out on agreed terms or conditions. In BMT Al-Amanah the profit sharing ratio differs only in calculation or distribution, there is a 50:60 ratio sharing 50:50 depending on the agreement made by both parties, then the benefits or positive impact can help members in saving funds or in funding funds, and can